2022
DOI: 10.1038/s41598-022-13088-2
|View full text |Cite
|
Sign up to set email alerts
|

Social networks respond to a disease challenge in calves

Abstract: Changes in network position and behavioral interactions have been linked with infectious disease in social animals. Here, we investigate the effects of an experimental disease challenge on social network centrality of group-housed Holstein bull dairy calves. Within group-housed pens (6/group) calves were randomly assigned to either a previously developed challenge model, involving inoculation with Mannheimia haemolytia (n = 12 calves; 3 calves/group) or a control involving only saline (n = 12 calves; 3 calves/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…These quantitative criteria are primarily based on the reported interindividual distance of 2 m to two horse lengths, within which horses only tolerate close affiliates [12,13,27,38,39,54,[115][116][117] and include measurements of spatial proximity between two horses, the number and duration of affiliative or agonistic interactions per hour and recording the nearest neighbour. In addition, recent studies have incorporated social network analysis to examine indirect connections beyond the dyad level and analyse the patterns of individual and group-level social interactions [41,52,[118][119][120][121].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These quantitative criteria are primarily based on the reported interindividual distance of 2 m to two horse lengths, within which horses only tolerate close affiliates [12,13,27,38,39,54,[115][116][117] and include measurements of spatial proximity between two horses, the number and duration of affiliative or agonistic interactions per hour and recording the nearest neighbour. In addition, recent studies have incorporated social network analysis to examine indirect connections beyond the dyad level and analyse the patterns of individual and group-level social interactions [41,52,[118][119][120][121].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of a more nuanced qualitative assessment of equine social behaviour with quantitative approaches may greatly assist equine welfare assessment and optimization, as poor welfare conditions, such as high population density (< 331 m2 per horse), may reduce equine sociality and skew horses' social behavioural repertoire toward agonistic interactions [80,122,123]. Changes in social behaviour have also been associated with disease in various group-living species ranging from honeybees, zebrafish and mice to calves and humans [121,[124][125][126][127], but the link between social networks and health has not yet been explored for horses. The changes seem species-specific, as mice reduce social interactions, while rhesus macaques and calves increase affiliative interactions with familiar conspecifics [121,128,129].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calves that are showing signs of disease are often dull and depressed, lying away from the rest of the group and appear less inquisitive. It has been shown that before a disease incidence, calves alter their behaviour, reducing the amount of play behaviour and social interactions with the calves around them (Burke and others 2022). On approaching the pen, calves should respond by either moving away from the observers, or curiously moving closer to them.…”
Section: Individual Examinationmentioning
confidence: 99%